Text, Topos, and the Awareness of History in Frédéric Mistral's Poème du Rhône. (2nd October 2019) - Bauer, Dominique
ABSTRACT: Frédéric Mistral (1830–1914) transforms historical awareness and local historiographies into a literary answer to some of the fundamental challenges of the modern world. It is argued here that the particularities of Mistral's 'empaysement'—textual abundance, multiple narrative identities, intertextuality, and storytelling—reflect not only an effort to preserve a pre-industrial agrarian society, but also testify to a modern awareness of the present as a future past, which explicitly structures the Poème du Rhône (1897) and Mireille (1859).